Optimization of extracellular lipase production by thermotolerant bacteria isolated from a hot spring - Alli Malar A/P Harikrishnan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
There is high demand for lipase globally where more than 1000 tons of it produced each year. A lipase produced from thermophilic bacteria is revised to have the advantage of thermal stability at 65C-70C, which makes them good candidates for lipid modifications which is most effective at high temperature. Thus, main focus of this research is to find the best lipase producing thermotolerant bacteria on its optimum condition of fermentation. The first step on finding lipase producer is to screen the isolated thermotolerant bacterial strains on tributyrin agar plate to check for zone of hydrolysis. Then, followed by screening under submerged fermentation. Next, lipase assay was carried out to find out the best lipase producer among the strains and finally the optimum condition for producing lipase investigated.